An exploratory study focusing on teaching and learning practices at the tertiary level in Pakistan: A case study of a public sector university. (March 2019) - Khan, Asif; Khan, Samina; Turi, Sajid
Abstract: Very few qualitative studies focusing on teaching and learning practices at the tertiary level have emerged from Pakistan. The present study, which applied a qualitative approach, examined those contextual and institutional factors that have a direct link with teaching/learning practices at the tertiary level in Pakistan. While exploring the said phenomenon, the study exclusively focused on three factors: 1) reading material, 2) course syllabi, and 3) teaching practices. The study noted that although there was a consensus among the university students and instructors regarding the satisfactory level of teaching and learning practices, some fundamental elements related to teaching and learning, were either ignored or missing.